The Gathering Place: Creating a Community Library in Collaboration with the Ditidaht First Nation - Clarke, Eva (2015)
The overall purpose of creating a community library with the Ditidaht First Nation is to increase opportunities for children to develop their oral language skills. In Chapter 1 I reflect on why oral language proficiency is a critical factor in early literacy development, specifically for First Nations children. I also identify how oral language is addressed within the current and draft British Columbia Ministry of Education English Language Arts curriculum documents. The community library initiative features the incorporation of a culturally responsive philosophy through practical activities such as storytelling by Ditidaht elders and dialogic reading as a way to increase language development within the children. In Chapter 2 I describe how dialogic reading and storytelling are situated within a sociocultural framework and review relevant research on these activities. In Chapter 3 I describe the processes that occurred in order to develop the Ditidaht community library. I also explain how the theories and research I reviewed in Chapter 2 underscored the activities I organized for the library and informed my teaching practices to develop the Ditidaht children’s oral language. The opportunities for dialogic reading and storytelling, as well as access to quality books through the use of the community library have contributed to strengthening the Ditidaht children’s ability to communicate. Graduate